Az Alkotmánybíróság a hatalmi ágak metszéspontjában - Tóth, J. Zoltán (Díké - A Márkus Dezső Összehasonlító Jogtörténeti Kutatócsoport folyóirata, 2025)
The principle of division of power in its modern form, as an institutional-functional principle of state organisation, was established during the Enlightenment in the 17th and 18th centuries and continues to evolve to this day. In addition to Montesquieu’s trias, i.e. the legislative, executive and judicial powers, new public law power factors have emerged over the last two and a half centuries. One of these factors is the centralised constitutional adjudication that emerged in 20th-century Europe, which, if effectively enforced, restructures the relationship between the other branches of power. This study uses the example of the Hungarian Constitutional Court to show how a centralised constitutional court affects the classical system of branches of power. The study concludes that the existence of the Constitutional Court does not eliminate the classical branches of power, but it does limit the functioning of the state organisations that embody them. These limitations arise not only from the principles of state organisation, but also from the values and principles of the constitution and from the fundamental rights enshrined therein. In exercising its powers, a typical European constitutional court – such as the Hungarian Constitutional Court – is now able to check and balance not only the political branches of power, but also any excesses of judicial power, i.e. the unconstitutional functioning of ordinary courts and the interpretation of law contrary to constitutional rights.